Substance use in Roma population in contact with social workers in the Czech Republic: A cross-sectional questionnaire survey - Chomynová, Pavla; Kozák, Jan; Mravčík, Viktor (Journal of ethnicity in substance abuse, 2021)
An increasing number of studies have focused on the topic of Roma communities and social exclusion in the Czech Republic, however, substance use has been surveyed only marginally. This paper brings new data on the patterns of substance use among Roma population in contact with social workers (546 respondents). Substance use, including daily smoking and regular excessive alcohol drinking, has been 2-6 times higher among Roma compared to the general population. Current illicit substance use was reported by 1/3 of the respondents (46.7% of males, 17.8% of females) with cannabis (27.1%) and methamphetamine (11.9%) being the most reported substances.
Keywords: poruchy spojené s užíváním psychoaktivních látek; Surveys and Questionnaires; Roma community; Substance-Related Disorders; Humans; smoking; Social exclusion; Alcohol Drinking; pití alkoholu; Female; Romové; Social Workers; sociální pracovníci; lidé; Roma; průzkumy a dotazníky; ženské pohlaví; Male; alcohol consumption; Czech Republic; Cross-Sectional Studies; illicit drug use; Česká republika; mužské pohlaví; průřezové studie